Muscle energy technique on non-specific knee pain associated with sacroiliac dysfunction - Antonelli, Gabriela; Outi, Melissa Yuka; Muller, Bruna Gomes; Binda, Aline Cristiane; Ruaro, João Afonso; Fréz, Andersom Ricardo (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Objective: to check the effectiveness of the increase on sacroiliac joint mobility on the painful knee among university students. Method: This was an experimental study with 13 students, from 18 to 25 years, which were subjected to an application of muscle energy technique in the sacroiliac joint. The knee functioning was assessed using the International Knee Documentation Committee Subjective Knee Form (IKDC). To classify the functioning was applied the International Classification of Functioning, Disability and Health generic core set. As for pain assessment, it was used the visual analog scale (VAS). Results: in initial evaluation, the referred pain was 6.1±1.3. After intervention was observed significant difference (p=0,0009), and reported pain of 3.3±2.7. Conclusion: a muscle energy technique applied in sacroiliac joint can be used for reduction of unspecific painful symptomatology of knee joint.